Prevalence and Nature of Structural Brain Abnormalities in Batterers: A Magnetic Resonance Imaging Study. Issue 3 (3rd July 2019) - Bueso-Izquierdo, Natalia; Verdejo-Román, Juan; Martínez-Barbero, José Pablo; Pérez-Rosillo, Miguel Ángel; Pérez-García, Miguel; Hidalgo-Ruzzante, Natalia; Hart, Stephen D.
Abstract: Introduction: Past research has found differences in the brain activation of batterers vs. other offenders in response to depictions of violence, but it is not known whether these functional differences are associated with structural brain abnormalities (SBAs). Objective: Investigate the prevalence and nature of SBAs in batterers using neuroimaging methods. Method: Two neuroradiologists independently diagnosed SBAs based on Magnetic Resonance Imaging scans for the 21 batterers and 20 other offenders. All participants had been screened to ensure that they had no obvious brain damage secondary to neurological injury or insult, including traumatic brain injury. Results: One participant had both a major and minor SBA; 13 had one or more minor SBAs. Most were judged to be not clinically relevant. Conclusion: SBAs are not strongly or specifically associated with IPV, and it is unlikely they are responsible for the differences in brain functioning between batterers and other offenders observed in past research.